Public value co-creation: A pedagogical approach to preparing future public administrators for collaboration. Issue 3 (October 2019) - Henson, Cassandra R
As the realm of public service and its relative partnerships (both social and economic) continues to change, so must the leadership charged with managing it. Gone are the days when a single government purview was sufficient for managing public service delivery, focused on preconceived notions of what citizens supposedly want. Public value and the lens of the public service professional must be wide enough to encompass the public–private sector partnerships that foster routine service delivery as well as concepts that help move it forward. A well-rounded public service professional needs a well-rounded educational foundation, creating the ability to operate in any economic sector. In this article, we discuss public value co-creation in the context of public trust, the value-based agenda and participatory governance. We then present findings from the General Social Survey and suggest a pedagogical approach to preparing future public administrators for the public value co-creation process.